(untitled) (Web of Teachers: Inderscience Research, 2026)
This article systematically covers the theoretical foundations and practical methods of integrating trigonometric functions. The main attention is paid to the integration of sine, cosine, tangent, cotangent and their expressions in power and product forms, the article shows the procedure for effective use of trigonometric functions, the method of changing variables. Each method is reinforced with step-by-step solved examples.